1995
DOI: 10.1029/95jd01532
|View full text |Cite
|
Sign up to set email alerts
|

Location of lightning discharges from a single station

Abstract: A new computer‐based ELF/VLF system for locating lightning discharges has been developed. Both the arrival azimuths of atmospherics and the distances to their sources are estimated. The direction‐finding technique uses the Poynting vector calculated directly in the time domain over the full band pass of the receiver. Both the distance of the lightning discharge and the ionospheric height can be estimated from the phase spectrum of the first‐order mode of the Earth‐ionosphere waveguide. The latter is approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 15 publications
(12 reference statements)
1
41
0
1
Order By: Relevance
“…Transverse resonance of the Earth-ionosphere cavity is observed at ELF-VLF frequencies which is well documented and interpreted (e.g. Rafalsky et al, 1995). The transverse resonance frequencies are f p = p c 2h , where p=1, 2, .…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Transverse resonance of the Earth-ionosphere cavity is observed at ELF-VLF frequencies which is well documented and interpreted (e.g. Rafalsky et al, 1995). The transverse resonance frequencies are f p = p c 2h , where p=1, 2, .…”
Section: Introductionmentioning
confidence: 76%
“…Nickolaenko and Hayakawa, 2002). Special observations of transverse resonance were reported in a few works (Belyaev, 1991;Lazebnyi et al, 1988;Rafalsky et al, 1995;Shvets, 1997;Shvets and Hayakawa, 1998;Brundel et al, 2002;Shvets, 2008). Significant maxima of the power spectra were found at multiples of the frequency ∼2 kHz at the middle and low latitudes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…One such technique was validated by comparing the single station determined positions with those reported by a commercial lightning detection network . Making use of 85 sferics observed at near Darwin, Australia, it was found that the 68% accuracy limits for the "Kharkov" single station lightning location method (developed by Rafalsky et al, 1995) were ∼4 • in bearing and ∼73 km in range . In this paper we will concentrate upon an another approach which makes use of the considerable sferic power present in the VLF band (3-30 kHz), such that very-long range remote sensing is possible; these VLF signals can be received thousands of kilometres from the source (Crombie, 1964)), as the electromagnetic energy propagates with low attenuation inside the waveguide formed by the conducting Earth and the lower boundary of the ionosphere, termed the Earth-Ionosphere Waveguide (EIWG).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques have been developed to allow a single-station lightning location (which might be more appropriate for an aircraft or vessel), often by combining a direction finding method with a procedure by which the distance of the lightning discharge can be estimated (see the review in Rafalsky et al (1995)). One such technique was validated by comparing the single station determined positions with those reported by a commercial lightning detection network .…”
Section: Introductionmentioning
confidence: 99%